Winner profile of Extraordinary Prize of Secondary Education in Galicia (Spain) - Ferreiro-Seoane, Francisco Jesús (2019)
This research aims to analyze if there is a profile of the students who win the “Extraordinary Prize of Secondary Education” (ESO) in Galicia (Spain). For this, the results of the totality of the students who competed for this prize will be compared according to their gender, habitat, ownership, and the level of formation of their parents. The initial working hypothesis was that if there would be no significant differences either in the group that opts for the prize, or between those who win it –6.57% of the students competing–, because they are the students with the highest academic performance. In order to analyze these profiles, the study considered the performance in all the subjetcts of the Extraordinary ESO Prize of the 1,522 students who participated in the contest for the period 2008-2013 in Galicia (Spain). The main conclusion is that the initial hypothesis is not fulfilled, given that the variables analyzed do influence the performance of the students who compete for the award. Gender has influence on all subjects, favoring male students; habitat does on 57% of subjects, ownership on 42.8%, and parent education on 85.7%. Bearing this in mind, the profile would be that of a student from a private and urban school, with parents with higher education.